Characterization of tolvaptan response and its impact on the outcome for patients with heart failure. Issue 4 (October 2021) - Hitomi, Yasuhiro; Nagatomo, Yuji; Yukino, Midori; Yumita, Yusuke; Kagami, Kazuki; Yasuda, Risako; Toya, Takumi; Namba, Takayuki; Masaki, Nobuyuki; Yada, Hirotaka; Adachi, Takeshi
Highlights: Diuretic response is an important factor in determining resistance to heart failure. Tolvaptan response was associated with subsequent clinical outcome. Association of tolvaptan response with repeated heart failure readmission was noted. Tolvaptan response can be informative when considering advanced care planning. Abstract: Background: Conventional diuretic therapy such as loop diuretics is a cornerstone of the treatment for heart failure (HF). Diuretic response is an important factor in determining resistance to HF therapy and has been shown to be associated with subsequent clinical outcome. Tolvaptan (TVP), a vasopressin V2 receptor antagonist, has a favorable profile in terms of rapid fluid removal and less aggravation of renal function. We hypothesized that the response to TVP might be associated with the subsequent clinical outcome. Method: In this single-center retrospective study, 148 consecutive HF patients who were administered TVP from 2014 through 2018 [age 79 (69–86) years, male 89 (60%)] were included. Ninety-six patients were divided into TVP responder [ N = 39 (41%)] and non-responder groups based on the cut-off value of gained urine output (+ 93 ml/mg TVP /day) on the day after TVP was introduced. Results: Early TVP introduction ( p = 0.012) and lower dose of loop diuretics ( p = 0.043) were predictors of TVP responder. For 2 years after discharge, TVP responders showed more favorable outcomes regarding the primary endpoint defined as the composite of all-cause death and HF readmission ( p = 0.034, log-rank test) and HF readmission ( p = 0.005). A multivariable Cox model analysis revealed that TVP responder was an independent predictor of the primary endpoint (hazard ratio 0.48, p = 0.041). TVP responders had a lower number of HF readmissions over a 1-year period ( p = 0.002). TVP response was independently associated with the number of HF readmissions ( p = 0.015). The proportion of patients with an extended period between discharge and HF readmission after TVP administration was higher in responders than non-responders (67% vs. 23%, p = 0.006). These associations of TVP response and post-discharge outcomes were more evident in patients who continued TVP after discharge. Conclusion: TVP response can be indicative of subsequent clinical outcomes and may be informative when considering advanced care planning. Graphical abstract: Image, graphical abstract